1995
DOI: 10.1037/0882-7974.10.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Age and health bias in practicing clinical psychologists.

Abstract: Psychological, social, and health variables were compared in 175 Black and White family caregivers of patients with dementia and 175 Black and White noncaregivers. Caregivers and noncaregivers did not differ within race on demographic variables. Caregiving was associated with increased depression and decreased life satisfaction only in White families. However, caregiving appears to have similar social consequences for Black and White families, including restriction of social activity and increased visits and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
1
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 28 publications
7
88
1
3
Order By: Relevance
“…A bias against older adults who are medically ill was demonstrated in a sample of mental health therapists (James and Haley 1995). Among medical providers, Gunderson and colleagues (Gunderson et al 2005) found that rurally-based physicians in the U.S. endorsed more negative views of "nursing home patients" compared to typical "older" patients, in terms of patients' ability to change health behaviors and to learn new health-related information, their ability to offer important input during a medical visit, and their personality traits (e.g., "less warm and accepting").…”
Section: Factors Associated With Ageism In the Medical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…A bias against older adults who are medically ill was demonstrated in a sample of mental health therapists (James and Haley 1995). Among medical providers, Gunderson and colleagues (Gunderson et al 2005) found that rurally-based physicians in the U.S. endorsed more negative views of "nursing home patients" compared to typical "older" patients, in terms of patients' ability to change health behaviors and to learn new health-related information, their ability to offer important input during a medical visit, and their personality traits (e.g., "less warm and accepting").…”
Section: Factors Associated With Ageism In the Medical Settingmentioning
confidence: 99%
“…Past research on patient factors in ageism, which has been primarily conducted among mental health providers, spawned the term "healthism" to describe negative perceptions of others based on poor health status, not purely on age (Gekoski and Knox 1990;James and Haley 1995). Because poor health is strongly associated with old age and older adult identity (Coupland and Coupland 1994;Vauclair et al 2015), the potential impact of "healthism" on the quality of patient-provider interactions and on care in the health care system is worthy of brief discussion.…”
Section: Factors Associated With Ageism In the Medical Settingmentioning
confidence: 99%
“…Adding old age to these considerations increases the risk of ageist behavior from professionals. There is abundant literature that considers ageist attitudes of social workers and human service students (Carmel, Cwikel, & Galinsky, 1992;James & Hayley, 1995;Kane, 1999Kane, , 2002Kane, , 2004aKane, , 2004bKane, , 2004cKane, , 2006aKane, , 2006bKane, , 2007Kane, , 2008; Kane, Hamlin, & Hawkins, 2004;Rohan, Berkman, Walker, & Holmes, 1995). Ageist attitudes influence the quality and type of services that are delivered to older persons and/or those deemed less worthy of care such as aging homeless persons (Bowling, 1999;Cykert, Kissling, Layson, & Hansen, 1995;Damiano, Momany, Willard, & Jogerst, 1997;Ivey, Wieling, & Harris, 2000;Kane, 2002Kane, , 2004aKane, , 2008Pettersen, 1995;Reekie & Hansen, 1992).…”
Section: Attitudes Toward the Homeless Young And The Homeless Oldmentioning
confidence: 97%
“…One issue is the necessity for psychotherapists to gain necessary training to work successfully in medical settings. Psychologists and other psychotherapists have been found to have negative biases about treating clients with medical problems (James & Haley, 1995), and increased training in collaborative care will be essential to prepare more psychotherapists to work effectively in medical settings. In addition, the evolution of business arrangements to make provision of psychological services in medical settings financially feasible and attractive for practitioners is essential.…”
Section: Clinical Issues and Summarymentioning
confidence: 99%